QUALITY OF POPULATION ADMINISTRATION SERVICES AT THE CITY OF CIREBON POPULATION AND CIVIL REGISTRATION SERVICE - Safila Dayarani, Dwi; Prapikasari, Putri; Nurfalah, Farida (Penerbit Lafadz Jaya, 2024)
Assessment of service standards at the Cirebon City Population and Civil Registration Service. Public service is the provision of services by an institution or organization in response to community needs. The aim of this research is to assess the quality of service at the Cirebon City Population and Civil Registration Service and ensure whether it meets community expectations. Strategies for overcoming service barriers. Descriptive qualitative research methods were implemented in this research. Interviews, documentation, and observation are data collection procedures. The research results show that the public is not completely satisfied with the services provided. The difficult process of getting a queue number, less than optimal information dissemination and public awareness are challenges in service. Meanwhile, the supporting factors are adequate facilities, empathy, security guarantees, cost certainty and good timeliness. To ensure good and satisfactory service, it is very important to implement necessary improvements by involving the community and evaluating community complaints to improve service quality.